Giant steps the new generation of African American writers - Young, Kevin A. (New York Perennial, 2000)
Giant steps presents a vibrant and wonderfully diverse collection of young black writing.
Randall Kenan: Now why come that is? -- Harryette Mullen: She landed on the moon ; Roadmap ; from Muse & Drudge ; Suzuki method ; Black Nikes -- Kevin Powell: Letter to my father -- Claudia Rankine: American light ; Him ; Overview is a place ; The quotidian ; This life -- Darieck Scott: 1979 -- Danzy Senna: The land of Beulah -- Reginald Shepherd: The difficult music ; Desire and the slave trade ; Antibody ; S'il meurt ; Icarus on Fire Island ; At the grave of Hart Crane ; Skin trade -- Natasha Tarpley: from Girl in the mirror -- Natasha Trethewey: At the station ; Speculation, 1939 ; Drapery Factory, Gulfport, Mississippi, 1956 ; Flounder ; Saturday matinee ; Bellocq's Ophelia -- Rebecca Walker: Higher yellow -- Anthony Walton: from Mississippi -- Philippe Wamba: Of prophets and madmen -- Colson Whitehead: The all-night bodega of souls -- Daniel Jerome Wideman: Singing sankofa -- Joe Wood: The yellow Negro -- Kevin Young: Nineteen seventy-five ; No offense ; Negative ; Charlie Chan on horn ; Langston Hughes ; Homage to Phillis Wheatley.
Includes bibliographical references (pages 345-351) and index.
Discography: pages 353-357.
Keywords: African Americans -- Literary collections; American literature -- African American authors